A Native LH1–RC–HiPIP Supercomplex from an Extremophilic Phototroph - Kazutoshi Tani; Ryo Kanno; Kenji V. P. Nagashima; Mai Kawakami; Naho Hiwatashi; Kazuna Nakata; Sakiko Nagashima; Kazuhito Inoue; Shinichi Takaichi; Endang R. Purba; Malgorzata Hall; Long-Jiang Yu; et al. (Communications Biology)
Abstract Halorhodospira (Hlr.) halophila strain BN9622 is an extremely halophilic and alkaliphilic purple phototrophic bacterium and has been widely used as a model for exploring the osmoadaptive and photosynthetic strategies employed by phototrophic extreme halophiles that enable them to thrive in hypersaline environments. Here we present the cryo-EM structures of (1) a unique native Hlr. halophila triple-complex formed from light-harvesting (LH1), the reaction center (RC), and high-potential iron–sulfur protein (HiPIP) at 2.44 Å resolution, and (2) a HiPIP-free LH1–RC complex at 2.64 Å resolution. Differing from the LH1 in the Hlr. halophila LH1–LH2 co-complex where LH1 encircles LH2, the RC-associated LH1 complex consists of 16 (rather than 18) αβ-subunits circularly surrounding the RC. These distinct forms of LH1 indicate that the number of subunits in a Hlr. halophila LH1 complex is flexible and its size is a function of the photocomplex it encircles. Like LH1 in the LH1–LH2 co-complex, the RC-associated LH1 complex also contained two forms of αβ-polypeptides and both dimeric and monomeric molecules of bacteriochlorophyll a. The majority of the isolated Hlr. halophila LH1–RC complexes contained the electron donor HiPIP bound to the surface of the RC cytochrome subunit near the heme-1 group. The bound HiPIP consisted of an N-terminal functional domain and a long C-terminal extension firmly attached to the cytochrome subunit. Despite overall highly negative surface-charge distributions for both the cytochrome subunit and HiPIP, the interface between the two proteins was relatively uncharged and neutral, forming a pathway for electron tunneling. The structure of the Hlr. halophila LH1–RC–HiPIP complex provides insights into the mechanism of light energy acquisition coupled with a long-distance electron donating process toward the charge separation site in a multi-extremophilic phototroph.